Aminopeptidase N Activity Predicts 5-Year Survival in Colorectal Cancer Patients. Issue 5 (June 2015) - Sanz, Begoña; Perez, Itxaro; Beitia, Maider; Errarte, Peio; Fernández, Ainhoa; Blanco, Lorena; Estalella, Itziar; Loizate, Alberto; Irazusta, Jon; López, José I.; Larrinaga, Gorka
Background: Aminopeptidase N (APN; EC 3.4.11.2) is a membrane dimeric metallopeptidase involved in differentiation, development, and proliferative processes of several tissues. Recent studies have demonstrated the increased expression and activity of this enzyme in several cancers. However, there are no available data about the impact of this peptidase in the biological aggressiveness and the survival of colorectal cancer (CRC) patients. Methods: The activity and mRNA expression of APN in tumor tissue (n = 81) and plasma (n = 40) of patients with CRC of low and high grades and stages were prospectively analyzed by fluorimetric and quantitative reverse transcriptase–polymerase chain reaction methods. Data obtained in adenoma and CRC were compared with those from the surrounding normal mucosa. Classic clinical and pathological parameters were stratified following APN data and analyzed for 5-year survival. Results: mRNA levels of APN ( ANPEP ) were lower in colorectal adenomas and adenocarcinomas than in the surrounding uninvolved mucosa (Kruskal-Wallis, P < 0.001). Aminopeptidase N activity in CRC tissue was higher in patients with better overall survival (log-rank P < 0.05, Cox analysis P < 0.05). By contrast, higher plasmatic APN activity correlated with worse overall survival (log-rank P < 0.01, Cox analysis P < 0.05). Conclusions: Aminopeptidase N activity in tissue and plasma from CRC patients is an independent prognostic factor of 5-year survival. The determination of APN activity levels in the plasma may be a safe, minimally invasive, and inexpensive way to define the aggressiveness of CRC in daily practice.